Analisis Capital Asset Pricing Model Dalam Pengambilan Keputusan Investasi Saham Studi Kasus: Perusahaan Yang Tergabung Di Indeks IDX30 - Selly Septiana; Dedi Hariyanto; Heni Safitri (Universitas Muhammadiyah Pontianak, 2018)
The purpose of this study was to determine the CAPM method used in making stock investment decisions in companies incorporated in the IDX30 Index. The results of research based on the analysis of Capital Asset Pricing Model states that investment decisions made on stocks are not efficient or not good, which is to consider selling these shares. The shares that have inefficient stock evaluation are: Adhi Karya, AKR Corporindo, Bank Rakyat Indonesia, Bank Mandiri Indonesia, Bumi Serpong Damai, Charoen Phokpand, Indofood Sukses Makmur, Lippo Karawaci, Matahari Department Store, Media Nusantara Citra, Gas Company State, PP Properti, Summarecon Agung, Sawit Sumbermas Sarana and Waskita Karya. The stocks that have efficient stock evaluation are: Adaro Energy, Astra International, Bank Central Asia, Bank Negara Indonesia, Gudang Garam, HM Sampoerna, Indofood CBP Sukses Makmur, IndoCement Tunggal Prakasa, Kimia Farma, Pakuwon Jati, Semen Gresik, Sri Rejeki Isman, Telekomunikasi Indonesia, United Tractors and Unilever Indonesia. Based on calculations and decisions to invest through the above CAPM method, the authors decide to invest in some companies with consideration of the company's shares affecting changes in the market with systematic risk (β) is good, have an efficient stock evaluation. The companies are Bank Central Asia, Bank Negara Indonesia, Gudang Garam, IndoCement Tunggal Prakasa, United Tractors and Unilever Indonesia.